2021
DOI: 10.1155/2021/5544916
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Associated Factors of Hypertension among HIV Patients

Abstract: Background. The dual burden of cardiovascular diseases and Human Immunodeficiency Virus (HIV) in sub-Saharan Africa is of public health concern. Persons living with HIV are 1.5–2 times more likely to develop CVD risk factors compared to the noninfected individuals. Hypertension is a major risk factor leading to the rising CVD epidemic in SSA. However, the burden of hypertension among HIV patients in Kenya is not well documented. Objective. This study determined the prevalence and the associated factors of hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
8
8
1
Order By: Relevance
“…42 Finally, this study finding showed that participants who had alcohol drinking experience were significantly associated with HTN. This finding is in agreement with studies done in Kenya 40 and Eastern Ethiopia. 8 This finding is also supported by clinical studies that state that chronic alcohol consumption of more than three drinks per day contributes to HTN incidence.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…42 Finally, this study finding showed that participants who had alcohol drinking experience were significantly associated with HTN. This finding is in agreement with studies done in Kenya 40 and Eastern Ethiopia. 8 This finding is also supported by clinical studies that state that chronic alcohol consumption of more than three drinks per day contributes to HTN incidence.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, older age was independently associated with HTN. This finding is in line with studies done in northeast Ethiopia, 20 southern Ethiopia, 39 Malaysia, 26 United States, 23 Parirenyatwa hospital, 29 Kenya, 40 Uganda, 24 and a cross-sectional study in Senegal. 41 The possible explanation could be stiffening of arterial vasculature, decreased viscoelasticity property of vessels, and resistance to blood flow occurs in older patients.…”
Section: Discussionsupporting
confidence: 91%
“…Lubega and al. in their study on prevalence and factors associated with hypertension among people living with HIV/AIDS on antiretroviral therapy in Uganda found that hypertension was related to increasing age 34,44 . In our study, individuals older than 45 years were 4 times more likely to suffer from hypertension.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have demonstrated that possible risk factors for hypertension in the HIV-infected population are old age, male gender, family history of HTN, long duration of HIV infection, low CD4 count, high viral burden, diabetes, high body mass index and certain medications combined with ART 16,43,44 . In our study HTN appears to be related to age, being overweight and obesity, diabetes, duration of HIV and the combined antiretroviral therapy for more than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to what was found in other studies among PWH. 21 , 22 This is not surprising as estrogen is believed to have a positive impact on the vasodilation of the vessels hence subsequent control of hypertension. 23 This implies that menopause is a major blow in every aging woman’s life since estrogen lowers.…”
Section: Discussionmentioning
confidence: 99%